2004
DOI: 10.1007/s00256-003-0678-1
|View full text |Cite
|
Sign up to set email alerts
|

Intraosseous malignant peripheral nerve sheath tumor with local recurrence, lung metastases and death

Abstract: Malignant peripheral nerve sheath tumor (MPNST) is almost always seen in soft tissue. Skeletal involvement by MPNST is uncommon and usually results from secondary invasion. Primary MPNSTs are exceptionally rare. We report a surgically proven case of intraosseous MPNST, with local recurrence and lung metastasis during follow-up. The imaging and histological features of the case are described and the literature on the subject briefly reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…Relative to muscle intensity, MRI usually shows an isointense lesion on T1W imaging and a hyperintense lesion on T2W imaging, with various patterns of enhancement depending on the degree of degeneration (3,9), as in our patient. Cortical thinning of the bone and invasion of the soft tissues around the bone are usually accepted as signs of malignancy, but have also been described in benign schwannoma (10).…”
Section: Discussionsupporting
confidence: 51%
“…Relative to muscle intensity, MRI usually shows an isointense lesion on T1W imaging and a hyperintense lesion on T2W imaging, with various patterns of enhancement depending on the degree of degeneration (3,9), as in our patient. Cortical thinning of the bone and invasion of the soft tissues around the bone are usually accepted as signs of malignancy, but have also been described in benign schwannoma (10).…”
Section: Discussionsupporting
confidence: 51%
“…An intraosseous MPNST may develop from minute, mainly unmyelinated nerve roots that accompany nutrient vessels and ramify within Volkmann’s canals and bone marrow (1416). To the best of our knowledge, only 19 cases of intraosseous MPNSTs, including the present study, have been reported in the literature to date (Table I) (610,17–29). There were nine male and 10 female patients, and the age at diagnosis ranged from 4–76 years.…”
Section: Discussionmentioning
confidence: 83%
“…A total of eight of the 19 cases (42%) occurred in the mandible or maxilla and six cases (32%) involved a vertebral body of the spine. Although <50% of MPNSTs arise in patients with NF1 (29), intraosseous MPNST cases were not associated with the hereditary NF1 syndrome, except for one case. The case of the present study was also not associated with NF1.…”
Section: Discussionmentioning
confidence: 91%
“…Malignant peripheral nerve sheath tumor is a rare soft tissue sarcoma arising from a peripheral nerve, typically in patients between the age of 20 and 50 [3], [7]. There is a strong association between MPNSTs and neurofibromatosis.…”
Section: Discussionmentioning
confidence: 99%
“…Of these 3 types of neurofibromas, MPNST's arise most frequently from plexiform neurofibromas [8], [11]. MPNSTs not originating from a neurofibroma can arise de novo from normal peripheral nerves or can occur secondary to prior radiation therapy [3], [7].…”
Section: Discussionmentioning
confidence: 99%